PENGARUH LITERASI KEUANGAN, TOLERANSI RISIKO, DAN FAKTOR DEMOGRAFI TERHADAP KEPUTUSAN INVESTASI MAHASISWA - Diva, Ida Bagus Brahmanda Kumala; Alit Suardana, Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023DO - 10.24843/EEB.2023.v12.i05.p02, 2023)
The development and progress of the modern era is followed by the development of financial products. With these developments, each individual needs to have sufficient ability and knowledge in managing finances and can increase their financial resources or wealth, such as investing. One of the investment instruments is capital investment through shares traded on the capital market. Regarding the capital market in Indonesia, currently it has been dominated by millennials, namely students with a dominance of 70%. However, before students or individuals start investing, there are several things that need to be considered, namely the financial literacy possessed by individuals and the risks faced by individuals. The purpose of this study is to provide empirical evidence regarding the effect of financial literacy, risk tolerance, and demographic factors on student investment decisions. The population in this study amounted to 466 students, with sampling using the method of determining the sample, namely purposive sampling, obtained 70 people. Analysis of the data used in this study is multiple linear regression analysis. This research suggests that. 1) Financial literacy have a positive effect on student investment decisions. 2) Risk tolerance have no effect on student investment decisions. 3) Demographic factors, namely gender, age, year of class, and income have no effect on student investment decisions.